Effect of permanent magnet stirring on solidification of Sn-Pb alloy. (15th October 2016) - Zeng, Jie; Chen, Weiqing; Yan, Wei; Yang, Yindong; McLean, Alex
Abstract: An experimental investigation has been conducted with respect to the influence of permanent magnet stirring (PMS) under different rotation speeds (ω = 60, 120 and 150 r/min) and center magnetic flux densities ( B = 757 and 1080 Gs) on the solidification of Sn-20 wt%Pb alloy. The magnetic field was generated by a pair of arc-shaped NdFeB permanent magnets with a gap that could be adjusted to obtain the required magnetic flux density. The effects of different values of ω and B were investigated by analyzing the driven flow intensity, surface and internal quality, macrostructure, microstructure and tensile properties. It was observed that with increasing ω and B there was significant improvement in the flow intensity of the liquid, surface pinholes, grain refinement and tensile properties. The results obtained have important implications for industrial metal casting processes. Graphical abstract: Highlights: Magnetic driven flow intensity of melt was evaluated by observing its surface trajectories. Surface pinholes and internal cavities were decreased by the permanent magnet stirring. Grain refinement was apparent with the increasing of rotation speed and magnetic flux density. Permanent magnet stirring leads to a significant increase in the tensile properties of Sn-Pb alloy.